(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study is dedicated to the comprehensive analysis and measurement of electrical current, voltage, and power in various types of circuits. The research emphasizes the correct use of measurement instruments, such as ammeters, voltmeters, and wattmeters, to achieve accurate and reliable readings. Experimental setups are designed to observe the behavior of electrical parameters under different conditions, including series and parallel circuits. The study also examines the relationship between current, voltage, and power, highlighting how variations in one parameter affect the others. Practical applications of these measurements are discussed, particularly in educational laboratories and engineering practices. The research provides a methodological approach for students and engineers to improve their understanding of fundamental electrical concepts and ensures safety and precision during measurement procedures.